2012
DOI: 10.1007/s12035-012-8239-z
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-Like Peptide 1 (GLP-1) Can Reverse AMP-Activated Protein Kinase (AMPK) and S6 Kinase (P70S6K) Activities Induced by Fluctuations in Glucose Levels in Hypothalamic Areas Involved in Feeding Behaviour

Abstract: The anorexigenic peptide, glucagon-like peptide-1 (GLP-1), reduces glucose metabolism in the human hypothalamus and brain stem. The brain activity of metabolic sensors such as AMP-activated protein kinase (AMPK) responds to changes in glucose levels. The mammalian target of rapamycin (mTOR) and its downstream target, p70S6 kinase (p70S6K), integrate nutrient and hormonal signals. The hypothalamic mTOR/p70S6K pathway has been implicated in the control of feeding and the regulation of energy balances. Therefore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 49 publications
5
40
0
Order By: Relevance
“…Similar data were observed in VMH, although the differences were not significant. These data are consistent with the results previously described in rodents [21,25,33,34]. However, exendin-4 treatment in fasted animals induced the activation of both metabolic sensors AMPK and S6K1 in a similar way to the re-feed condition, although exendin-4 treatment decreased blood glucose levels.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Similar data were observed in VMH, although the differences were not significant. These data are consistent with the results previously described in rodents [21,25,33,34]. However, exendin-4 treatment in fasted animals induced the activation of both metabolic sensors AMPK and S6K1 in a similar way to the re-feed condition, although exendin-4 treatment decreased blood glucose levels.…”
Section: Discussionsupporting
confidence: 92%
“…We have previously reported an anorexigenic effect of exendin-4 in lean and obese rats [24] and also suggested that this effect can be explained by the regulatory effect exendin-4 has on hypothalamic AMPK and S6K1 activities [25]. Food intake was similar in wild-type and PASK-deficient mice (Fig.…”
Section: Pask-deficient Mice Display Altered Feeding and Blood Glucosmentioning
confidence: 64%
See 3 more Smart Citations